Ordinary people, extraordinary wealth : the 8 secrets of how 5,000 ordinary Americans became successful investors, and how you can too - Edelman, Ric. 4 0 16; 5 (New York : HarperBusiness, 2001)
Presents eight basic principles of investing such as carrying a mortgage, contributing to employer retirement plans, investing on a diversified portfolio, managing money properly, and devoting less than three hours per week on finances, including some tips from successful investors.
Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; Investments;Finance, Personal;Investments.;Personal finance. -- United States.;United States; 20; 2